Comparing efficacy in reducing pulling and welfare impacts of four types of leash walking equipment - Johnson,Anamarie C.; Wynne,Clive D. L. (PeerJ, 2024)
Background Leash pulling is a commonly reported problem behavior for dog owners, as a result, a variety of leash equipment types are offered to mitigate pulling force. We were particularly interested in prong collars as their inherently aversive design has made their use a subject of debate. Though banned in certain countries and widely available in others, to date, there is no research comparing them to other leash walking equipment. Methods We compared four types of leash walking equipment: a martingale (flat collar as baseline measure), a front-connection harness, a polymer prong-style collar (Starmark), and a standard metal prong collar. Twenty-three dogs were walked on all four types of equipment for 5-min each. Equipment was attached to a leash which was connected to a battery-powered strain gauge to measure the dog’s pulling force. All walks were video recorded for behavior analysis. Results There were statistically significant differences among the leash equipment types in pulling impulse (Newtons × seconds), (χ2(2) = 30.6, p < 0.001). Post-hoc analysis revealed significant differences in impulse between the martingale and the other equipment: harness (Z = −3.69, p < 0.001), Starmark collar (Z = −3.62, p < 0.001) and prong collar (Z = −3.92, p < 0.001). No other differences among equipment types were significant. Fifteen behaviors were examined as welfare indicators but only three: looking at the handler, lip licking, and sniffing occurred across all dogs and all walks. There was a statistically significant difference in frequency of lip licking behavior across the four types of leash-equipment (χ2(2) = 8.17, p = 0.04) and post-hoc analysis showed a difference between the martingale and the harness (Z = −2.65, p = 0.008). While our research did not provide any clear evidence of poorer welfare due to equipment type, we caution the generalizability of these findings and recommend further assessment of these items of leash-walking equipment in real-life scenarios.
Keywords: Dog behavior; Tension; Walking; Harness; Prong collar; Behavior analysis